Ideal Dietary Intakes of Vitamin B12 and Vitamin E Prevent Anemia during Pregnancy - Siregar, Eka Darmayanti Putri; Amir, Arni; Irawati, Nuzulia (Poltekkes Kemenkes Jakarta III, 2024)
Anemia in pregnancy is one of the priority nutritional problems to be tended to. WHO in 2019 reported Anemia in 40% of pregnant women worldwide; in Indonesia, based on the 2018 Riskesdas was 48.9%, and in West Sumatra and Padang City, 18.10% and 17.70%. One of the causes of Anemia was a low intake of vitamins B12 and E. This study aimed to determine if serum ferritin levels and vitamin B12 and E consumption were correlated with those of third-trimester pregnant women. This analytical cross-sectional study was done from April to July 2022 at Lubuk Kilangan Public Health Center and Andalas University's Biomedical Laboratory. The population was 64 third-trimester pregnant women, and 42 samples were used using proportional stratified random and simple random sampling. A SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire) and Human ferritin kit DBC (Diagnostics Biochem Canada) examined by ELISA (Enzymed-Linked Immunosorbent Assays) were the instruments. The average of Vitamin B12 and vitamin E consumption daily was 7.71 µg and 5.87 mg, and serum ferritin was 10.53 µg/L. Serum ferritin levels were linked with vitamin B12 (r=0.879; p=0.001) and vitamin E (r=0.455; p=0.002) intake. Enough intake of vitamin B12 and vitamin E will lead to ideal serum ferritin levels.